2014
DOI: 10.4236/ojo.2014.410042
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Stability of Open-Wedge High Tibial Osteotomy: Comparison of Two Locking Plates

Abstract: Introduction: Recently, new plates with locking screws have been developed and used for medial open-wedge high tibial osteotomy (HTO). The purpose of this study was to evaluate and compare biomechanical properties of different internal fixations in open-wedge HTO using the two currently available locking plates. Methods: Eight paired fresh-frozen cadaveric lower extremities were vertically embedded in steel boxes. The axial compression load was applied to the legs using the mechanical testing machine. The axia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
2
12
1
Order By: Relevance
“…Stoffel et al (Stoffel et al 2004 ) also performed axial compression load to failure tests to compare the TomoFix plate to the Puddu plate (rectangular short spacer plate) by using composite bones and also reported a better axial stability for the TomoFix. Watanabe et al (Watanabe et al 2014 ) also performed a comparative study of the TomoFix and the Puddu plates by using cadaveric bones and reported the highest failure load for the TomoFix. None of the previously cited studies included the iBalance and the PEEKPower implants, whereas we did not include the Puddu plate.…”
Section: Resultsmentioning
confidence: 99%
“…Stoffel et al (Stoffel et al 2004 ) also performed axial compression load to failure tests to compare the TomoFix plate to the Puddu plate (rectangular short spacer plate) by using composite bones and also reported a better axial stability for the TomoFix. Watanabe et al (Watanabe et al 2014 ) also performed a comparative study of the TomoFix and the Puddu plates by using cadaveric bones and reported the highest failure load for the TomoFix. None of the previously cited studies included the iBalance and the PEEKPower implants, whereas we did not include the Puddu plate.…”
Section: Resultsmentioning
confidence: 99%
“…The plate did not lose its shape or weaken when the force was applied to it. Conversely, the lateral cortex of the tibial head had no such support, which caused this discrepancy in displacement between the two sides, as the lateral cortex is the weakest point of a MOWHTO (Maas et al , 2013; Watanabe et al , 2014; Diffo Kaze et al , 2015). Furthermore, the positive values at position LSZ and the negative values at position MSZ indicate a valgus malrotation of the tibial head.…”
Section: Discussionmentioning
confidence: 99%
“…This large difference within the synthetic and allograft groups between the two opposite cortices of the tibial head is likely to be due to the volume of the graft being much larger medially than laterally, in order to fit the shape of the osteotomy wedge. The synthetic group showed the highest stiffness medially but the lowest stiffness laterally, suggesting that this type of graft offers the least support to the lateral cortex, the weakest point of a MOWHTO (Maas et al , 2013; Watanabe et al , 2014; Diffo Kaze et al , 2015). This is further supported by the observed breaking up of the synthetic grafts at the lateral side during compression.…”
Section: Discussionmentioning
confidence: 99%
“…The allograft group withstood higher forces than the control group prior to construct failure, which may be explained by the added medial and lateral stiffness of the tibial head provided by the wedge (Fig 8). This added static stiffness may have reduced valgus malrotation of the tibial head, which likely helped to distribute the vertical force more evenly across the tibial head and lowered the stress on the lateral cortex, the weakest point of a MOWHTO [5, 21, 23]. Furthermore, a recent study [24] used a 3D finite element model to find that the way that loads are balanced between the medial and lateral compartments of the knee may be key in optimising the clinical outcome of the procedure.…”
Section: Discussionmentioning
confidence: 99%